The Impact of the Sarbanes-Oxley Act on Takeover Protection Provisions - Engkuchik , Engku N.S.; Kaya , Halil D. (Journal of Ecohumanism, 2024)
We investigate the effects of the Sarbanes-Oxley (SOX) Act on corporate governance metrics, such as the takeover protection provisions and the governance index (G-index). We look at provisions related to takeover protection such as severance agreements, indemnity contracts, golden parachutes, compensation schemes, director liability and indemnity. We examine the effects of SOX between the two periods, designating the 1998–2000 timeframe as the pre–SOX period and the 2002–2004 timeframe as the post–SOX period. Then, in order to determine whether these provisions were affected in any way after 2004, we compare the values from 2004 to the values from 2006. We discover that between the pre-SOX and post-SOX periods, the G-index mean score had increased, indicating a declining degree of total shareholder rights. When we examine the six protection provisions, we discover that two of them—compensation plans and golden parachutes—had deteriorated (i.e., the percentage of firms using these measures had increased) and four of them—indemnification contracts, severance agreements, director indemnity, and director liability—had improved. Put differently, following the passage of the Act, businesses began to select different takeover protection options. However, the SOX’s long-term effects were restricted to two variables only. After 2004, the proportion of companies employing golden parachutes climbed (i.e., negatively), whilst the percentage of companies utilizing severance agreements decreased (i.e., positively). We conclude that, in general, the SOX Act had a favorable effect on the majority of the measures that we looked at, with the exception of two measures: golden parachutes and compensation schemes.